(untitled) - Mehl-Madrona, Lewis (New York, 1998)
Coyote Medicine isn't about eschewing Western medicine when it's effective, but about finding other answers when medicine fails: for chronic sufferers, patients not responding to medication, or "terminal" cases that doctors have given up on. In the story of one doctor's remarkable initiation into alternative ways to spiritual and physical health, Coyote Medicine provides the key to untapped healing methods available today.
Keywords: Alternative medicine,Thuốc thay thế; United States,Hoa Kỳ